Wireless Security Network Using Authentication and Encryption - Dukitha, M; Sheeba, G (International Journal of Computer Sciences and Engineering, 2025)
The 21th Century is defined by human scientific breakthroughs. One of them is the global use of the Internet. Almost every educated person nowadays knows more or less about the internet. Thereby, a large percentage of the human populations make use of the internet on a daily basis. Wireless internet access is thereby made affordable and accessible for everyone and that has boosted human communication and economy development into a new era. However, along with benefits, wireless internet access also possesses several risks and threats of security. The Internet has become a fertile land for criminals of all kinds to operate. Most of the time what they try to take is personal information, some of them of extreme values and sensitivity, from naive and unaware users. In that sense, a comprehensive study on how cybercriminal carry out their attacks and how to avoid and actually prevent such attacks if possible would be beneficial for the righteous netizens.